2016
DOI: 10.1007/s12519-016-0035-9
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of HIV-infected anti-retroviral therapy naïve children from Mumbai, India

Abstract: Perinatal transmission is the most common mode of acquiring HIV infection in children. The Prevention of Parent to Child Transmission (PPTCT) program should be strengthened for lowering the transmission rate by providing extended ART to mothers during pregnancy and breast-feeding. Tuberculosis remains a major concern in HIV-infected children. The poor correlation between WHO clinical and immunological staging emphasizes the importance of making CD4 facilities available in HIV prevalent areas. Malnutrition cann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The Joint United Nations Program on HIV/acquired immunodeficiency syndrome (AIDS) showed that the incidence and mortality of HIV-infected children aged 0–14 years in Indonesia increased throughout the year in 2018 with 3,100 new cases and 2,200 deaths due to AIDS [ 3 ]. Diarrhea is one of the symptoms in HIV- infected children with an incidence rate between 9.9% and 24.5% [ 4 5 ]. HIV-infected children are 5.6 times more likely to experience diarrhea than non-HIV children [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Joint United Nations Program on HIV/acquired immunodeficiency syndrome (AIDS) showed that the incidence and mortality of HIV-infected children aged 0–14 years in Indonesia increased throughout the year in 2018 with 3,100 new cases and 2,200 deaths due to AIDS [ 3 ]. Diarrhea is one of the symptoms in HIV- infected children with an incidence rate between 9.9% and 24.5% [ 4 5 ]. HIV-infected children are 5.6 times more likely to experience diarrhea than non-HIV children [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it will be important to understand the survival in these children over this period of one and half decade. Though few Indian studies [12][13][14] have studied the outcomes in CLHAs, the sample has been small and restricted to a single centre. We propose to estimate the survival in a cohort of CLHAs and to study the factors associated with survival in CLHAs in government ART centres in Mumbai, India.…”
Section: Introductionmentioning
confidence: 99%